Love, Death, and Resurrection in the Musical Vision of Philip Glass, Franz Liszt, and Ancient Chant: A Recital by pianist and chanter Paul Barnes (21 June 2018) - Barnes, Paul (Journal of the International Society for Orthodox Music, 2020)
A recital programme, performed during the 2018 Pan-Orthodox Music Symposium "Orthodox Liturgical Music: Ancient & Modern Creativity", on 21 June 2018, in St Mary’s Orthodox Cathedral, Minneapolis, USA.